LDL PROTEIN NITRATION: IMPLICATION FOR LDL PROTEIN UNFOLDING - Hamilton, Ryan T. (2008)
Oxidatively- or enzymatically-modified low-density lipoprotein (LDL) is intimately involved in the initiation and progression of atherosclerosis. The in vivo modified LDL is electro-negative (LDL(−)) and consists of peroxidized lipid and unfolded ApoB-100 protein. This study was aimed at establishing specific protein modifications and conformational changes in LDL(−) assessed by liquid chromatography/tandem mass spectrometry (LC/MS/MS) and circular dichroism analyses, respectively. The functional significance of these chemical modifications and structural changes were validated with binding and uptake experiments to- and by bovine aortic endothelial cells (BAEC). The plasma LDL(−) fraction showed increased nitrotyrosine and lipid peroxide content as well as a greater cysteine oxidation as compared with native- and total LDL. LC/MS/MS analyses of LDL(−) revealed specific modifications in the apoB-100 moiety, largely involving nitration of tyrosines in the α-helical structures and β(2) sheet as well as cysteine oxidation to cysteic acid in β(1) sheet. Circular dichroism analyses showed that the α-helical content of LDL(−) was substantially lower (~25%) than that of native LDL (~90%); conversely, LDL(−) showed greater content of β-sheet and random coil structure, in agreement with unfolding of the protein. These results were mimicked by treatment of LDL subfractions with peroxynitrite (ONOO(−)) or SIN-1: similar amino acid modifications as well as conformational changes (loss of α-helical structure and gain in β-sheet structure) were observed. Both LDL(−) and ONOO(−)-treated LDL showed a statistically significant increase in binding and uptake to- and by BAEC compared to native LDL. We further found that most binding and uptake in control-LDL was through LDL-R with minimal oxLDL-R-dependent uptake. ONOO(−)-treated LDL was significantly bound and endocytosed by LOX-1, CD36 and SR-A with minimal contribution from LDL-R. It is suggested that lipid peroxidation and protein nitration may account for the mechanisms leading to apoB-100 protein unfolding and consequential increase in modified LDL binding and uptake to and by endothelial cells that is dependent on oxLDL scavenger receptors.